Beekeeping in Northeast Region of India - Patle, Naveen Kumar; Shitiri, Meribeni (Indian Horticulture, 2024)
Apiculture, also known as beekeeping, plays a pivotal role in the sustainable development of agriculture, serving as the fifth crucial element for the agricultural development. Furthermore, it stands as the fifth essential input for enhancing yields and ensuring the quality of production in cross-pollinated agricultural and horticultural crops. The Northeast of India boasts abundant floral resources,diverse plant life and an exceptionally favourable climate for honey production. However, the region has yet to unlock its potential as a ‘honey capital’ in the country, primarily due to the lack of awareness, insufficient skilled labour, limited integration of beekeeping with agriculture, and an inadequate supply of bee colonies for commercial cultivation. In this region, honey is sourced from both wild and cultivated beehives, with an estimated 40,000 beekeepers. A majority of these beekeepers operate at a marginal scale, managing just one or two beehives. Despite the significant role that beekeeping plays in generating employment and sustaining livelihoods, its full potential remains untapped.